2011
DOI: 10.1002/bmc.1672
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous estimation of 16α‐hydroxycleroda‐3,13(14) Z‐dien‐15,16‐olide from Polyalthia longifolia and its metabolite in hamster plasma: application to pharmacokinetic study

Abstract: A selective and sensitive LC-MS-MS method was developed and validated for simultaneous estimation and pharmacokinetic studies of 16α-hydroxycleroda-3,13(14) Z-dien-15,16-olide (K-09) obtained from Polyalthia longifolia and its metabolite (K-9T), a novel antidyslipidemic agent. Sample clean-up involved liquid-liquid extraction of both the analytes and internal standard (rosuvastatin) from 200 μL of hamster plasma. The analytes were chromatographically separated on a Symmetry-Shield C₁₈ (5 µm, 4.6 × 150 mm) colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…11,12 Of the clerodane diterpenoids identified in this study, compound 6 was most abundantly present in the active fraction of the P. longifolia extract and highly active against several plant pathogenic fungi and bacteria. In previous studies, compound 6 has been reported as a chemotaxonomic marker exhibiting a wide range of biological and pharmaceutical activities, including as caterpillar antifeedant 9 and antileishmanial, 10 anticancer, 36 antidyslipidemic, 37 antihyperlipidemic, 37 and antimicrobial activities. 38,39 For the initial structure− activity relationship study, the γ-hydroxyl group at C-16 of 6 was acetylated in this study, and we found that the acetate analogue (6a) lost its antifungal activities (Table 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11,12 Of the clerodane diterpenoids identified in this study, compound 6 was most abundantly present in the active fraction of the P. longifolia extract and highly active against several plant pathogenic fungi and bacteria. In previous studies, compound 6 has been reported as a chemotaxonomic marker exhibiting a wide range of biological and pharmaceutical activities, including as caterpillar antifeedant 9 and antileishmanial, 10 anticancer, 36 antidyslipidemic, 37 antihyperlipidemic, 37 and antimicrobial activities. 38,39 For the initial structure− activity relationship study, the γ-hydroxyl group at C-16 of 6 was acetylated in this study, and we found that the acetate analogue (6a) lost its antifungal activities (Table 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The liquid chromatography mass spectrometer (LC-MS/MS) provides a useful separation and detection technique for the determination of drug in biological matrices with enviable accuracy, sensitivity, selectivity, robustness and shorter run time. [13][14][15] To support the pharmacokinetic and metabolism study of diapocynin, an accurate, rapid and reproducible bioanalytical method was essential. To the best of our knowledge, pharmacokinetic characteristics of diapocynin have been unexplored.…”
Section: Introductionmentioning
confidence: 99%